Historic Titles and Historic Rights in the Law of the Sea in the Light of the South China Sea Arbitration. (3rd April 2017) - Kopela, Sophia
ABSTRACT: Historic titles and historic rights have been a complicated issue in the law of the sea both conceptually and practically. The South China Sea Arbitration between the Philippines and China raised important issues regarding the contemporary relevance and validity of historic claims, and the relationship between the Law of the Sea Convention and historic rights. This articles examines historic rights and historic titles in the law of the sea in the light of the South China Sea Arbitration and evaluates the contribution of the Tribunal's Awards to the clarification of these concepts.